Thyroxine-Induced preradial myxedema - Mary Zothanpuii Chhangte; Shikha Verma; Binod Kumar Thakur; Anita Marak (Wolters Kluwer Medknow Publications, 2019)
Localized myxedema is most commonly described in patients with hyperthyroidism, especially Graves' disease. Although pretibial myxedema generally appears as indurated plaques on the shins, it has also been rarely reported in other areas such as the face, shoulders, arms, and abdomen. We report a rare case of preradial myxedema in a hyperthyroid patient who was taking thyroxine post thyroidectomy for goiter. To the best of authors' knowledge, this is the first case of preradial myxedema, due to long-term intake of thyroxine, reported in the English dermatological literature.